2018
DOI: 10.1155/2018/5387896
|View full text |Cite|
|
Sign up to set email alerts
|

Usability Assessments for Augmented Reality Motor Rehabilitation Solutions: A Systematic Review

Abstract: This article aims to understand which methods and user assessment approaches are most commonly used in motor rehabilitation studies that use Augmented Reality (AR) applications. The way in which this was performed and discussed was through a systematic review of the area. Firstly, the different uses of AR in these treatments, and the importance of improving usability studies to evaluate these interfaces and their interactions with their users, were discussed. Then, the systematic review of the literature was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 43 publications
0
9
0
2
Order By: Relevance
“…Only 4 out of the 20 (20%) [ 29 , 36 , 37 , 46 ] included reviews briefly mentioned any characteristic of the evaluators' profile. One of the reviews [ 36 ] reported that one of the 32 articles included mentioned that the person who performed the usability assessment was a blind evaluator.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only 4 out of the 20 (20%) [ 29 , 36 , 37 , 46 ] included reviews briefly mentioned any characteristic of the evaluators' profile. One of the reviews [ 36 ] reported that one of the 32 articles included mentioned that the person who performed the usability assessment was a blind evaluator.…”
Section: Resultsmentioning
confidence: 99%
“…Only 4 out of the 20 (20%) [ 29 , 36 , 37 , 46 ] included reviews briefly mentioned any characteristic of the evaluators' profile. One of the reviews [ 36 ] reported that one of the 32 articles included mentioned that the person who performed the usability assessment was a blind evaluator. One review stated that several studies (exact numbers not provided) used graduate students as both evaluators to perform usability inspections and participants in experimental sessions (eg, think-aloud protocol, remote user testing) [ 37 ], whereas another review [ 46 ] reported that usability evaluations were conducted by researchers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thanks to the miniaturization of the devices and the commercial development of affordable products, wearable technology-assisted devices appear to be an interesting tool for gait rehabilitation in overground condition (i.e., gait training without treadmill) [ 18 , 19 , 20 , 21 ]. Among existing tools, AR technology does not fully immerse the user in a simulated environment but superimpose virtual elements over the real-world.…”
Section: Introductionmentioning
confidence: 99%